Databases for effective bibliometric analysis: a quick guide - Abd Rahman, Nurul Hayani; Mohamed Isa, Zuraidah; Anuar, Azyyati (Universiti Teknologi MARA, Kedah, 2025)
Bibliometric analysis has become an essential tool for evaluating research outputs, uncovering trends, and charting the scientific landscape across disciplines. This review highlights key databases commonly used in bibliometric studies, emphasizing their importance in terms of scope, coverage, and functionality. Selecting the most suitable database ensures that bibliometric analyses are accurate and comprehensive, enabling researchers to draw reliable conclusions and insights. Bibliometric analysis is a quantitative approach used to assess and analyze scholarly output, including academic publications and citation patterns. It aids in evaluating research performance, identifying key studies, and detecting emerging trends within various fields. The success of bibliometric research largely depends on selecting the right database. This paper reviews two prominent databases frequently used in bibliometric analysis: Web of Science (WoS) and Scopus.